Investigation of the mouse cerebellum using STIM and µ-PIXE spectrometric and FTIR spectroscopic mapping and imaging - Hackett, Mark; Siegele, R.; El-Assaad, F.; McQuillan, J.; Aitken, J.; Carter, E.; Grau, G.; Hunt, N.; Cohen, D.; Lay, P. (Elsevier B.V., 2011)
The cerebral biochemistry associated with the development of many neurological diseases remains poorly understood. In particular, incomplete understanding of the mechanisms through which vascular inflammation manifests in tissue damage and altered brain function is a significant hindrance to the development of improved patient therapies. To this extent, a combination of spectrometric/spectroscopic mapping/imaging methods with an inherent ability to provide a wealth of biochemical and physical information have been investigated to understand further the pathogenesis of brain disease. In this study, proton-induced X-ray emission (PIXE) mapping was combined with scanning transmission ion microscopy (STIM) mapping and Fourier-transform infrared (FTIR) imaging of the same tissue sample to study directly the composition of the murine (mouse) cerebellum. The combination of the elemental, density and molecular information provided by these techniques enabled differentiation between four specific tissue types within the murine cerebellum (grey matter, white matter, molecular layer and micro blood vessels). The results presented are complementary, multi-technique measurements of the same tissue sample. They show elemental, density and molecular differences among the different tissue types.